Effect of dietary nucleotides on small intestinal repair after diarrhoea. Histological and ultrastructural changes. Issue 7 (July 1994) - Bueno, J; Torres, M; Almendros, A; Carmona, R; Nuñez, M C; Rios, A; Gil, A
Abstract : The effects of specific nutrients on intestinal maturation and repair after injury are practically unknown. The purpose of this work was to study the effects of dietary nucleotides on the repair of the intestinal mucosa after chronic diarrhoea induced by a lactose enriched diet in the weanling rat. One group of weanling rats was fed with a standard semipurified diet (control group), and another group was fed with the same diet containing lactose as the only soluble carbohydrate (lactose group). After 14 days the lactose group was allowed to recover for four weeks with the control diet (lactose-control group) or with the control diet supplemented with AMP, GMP, IMP, CMP, and UMP 50 mg/100 g each (lactose-nucleotide group). The control group was divided into two subgroups, which were fed with the control diet and the nucleotide supplemented diet for the same period (control-control group and control-nucleotide group). The lactose diet induced diarrhoea after 24 hours of feeding. Two weeks later there were changes in intestinal structure with loss of enterocyte microvillar surface, significant lymphocyte infiltration, supranuclear cytoplasmic vesiculation, decreased number of goblet cells, and enlarged mitochondria with low density and few cristae. After recovery from diarrhoea, animals fed the nucleotide enriched diet showed an intestinal histology and ultrastructure closer to that of the normal control group. Mitochondrial ultrastructure was closer to normal in comparison with the lactose-control diet group. In this second group the number of goblet cells as well as the villous height/crypt depth ratio was reduced and the number of intraepithelial lymphocytes increased compared with the nucleotide supplemented group. These results suggest that dietary nucleotides may be important nutrients for intestinal repair.